2016
DOI: 10.1037/ppm0000059
|View full text |Cite
|
Sign up to set email alerts
|

The role of location in everyday experiences of music.

Abstract: Mehrabian and Russell's (1974) Pleasure-Arousal-Dominance model states that a propensity to approach/avoid an environment can be conceptualized in terms of the pleasure and arousal it elicits and one's degree of dominance therein. Using the Experience Sampling Method, 177 individuals provided responses concerning Mehrabian and Russell's model throughout one week regarding music experiences that occurred in their daily life (including how the music was heard and how their responses related to the listening loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 35 publications
5
36
0
Order By: Relevance
“…These results can be interpreted meaningfully in terms of Mehrabian and Russell's () PAD model. In particular, although previous research has tended to ignore the dominance dimension, the present findings indicate that, at least in the context of music, the control dimension can make a useful contribution to the understanding of responses to the environment, even when controlling for a number of additional variables: this supports the conclusions of recent research (e.g., Krause & North, ; Krause, et al ., ). Support for the full, three factor model with regard to music listening came from the main analyses: the present results confirm that dominance, operationalized as degree of control over the music, was related to an individual's response to both the music and to the overall situation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…These results can be interpreted meaningfully in terms of Mehrabian and Russell's () PAD model. In particular, although previous research has tended to ignore the dominance dimension, the present findings indicate that, at least in the context of music, the control dimension can make a useful contribution to the understanding of responses to the environment, even when controlling for a number of additional variables: this supports the conclusions of recent research (e.g., Krause & North, ; Krause, et al ., ). Support for the full, three factor model with regard to music listening came from the main analyses: the present results confirm that dominance, operationalized as degree of control over the music, was related to an individual's response to both the music and to the overall situation.…”
Section: Discussionmentioning
confidence: 97%
“…All participants were asked to listen to 15 minutes of music in a particular situation, namely in the laboratory, while commuting on public transportation, or while at the gym. The gym and commuting conditions represent two common, everyday listening contexts, as denoted by previous experience sampling method research (e.g., Greasley & Lamont, ; Krause, North & Hewitt, ; North et al ., ). Additionally, they differ with regard to expected level of arousal associated with the setting (e.g., Krause & North, ; North & Hargreaves, , ).…”
Section: Methodsmentioning
confidence: 99%
“…The third study (Krause, North & Hewitt, 2013c) shifted the focus to the nature of the locations within which music was heard and how it was heard. The study identified 11 locations in which people have reported frequently listening to music (at home, driving a car, at work, on public transport, in a car, other, at a friend's house, walking, at the gym, restaurant, and the pub/club), and the results supported the hypothesis that people's reactions to music in everyday life are influenced by the characteristics of the listening context.…”
Section: Dominance and Controlmentioning
confidence: 99%
“…For instance, North and Hargreaves [5] found that listeners preferred high arousal versions of a piece while exercising and low arousal versions of the same piece while relaxing. More recently, researchers have investigated both the contexts and the activities that are associated with music, finding differences in both [1,3,6]. For instance, music in the gym is found to be more motivating than music in a restaurant [6].…”
Section: Introductionmentioning
confidence: 99%
“…More recently, researchers have investigated both the contexts and the activities that are associated with music, finding differences in both [1,3,6]. For instance, music in the gym is found to be more motivating than music in a restaurant [6]. Greb, Schlotz and Steffens [7] directly compared the effects of individual and situational influences on different functions of music listening, asking participants to imagine and then describe self-chosen listening situations.…”
Section: Introductionmentioning
confidence: 99%